Survey of Physical Fitness And Mental Health Levels At SSB Putra Wirasaba - M.Rizaldy Putra Setiabudi; Zhillan Fadilah Akbar; Muhammad Arief Setiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Physical fitness has a very important role in improving bodily health and mental performance, especially in the educational context. This study aims to analyze the influence of football on the level of physical fitness and health of SSB Putra Wirasaba members. Football, as a physical activity that is carried out intensively, is believed to improve physical condition, endurance and concentration. Apart from that, good physical fitness also has a positive impact on mental health, reduces stress, and increases the ability to carry out learning and teaching activities. This research uses a qualitative method with a descriptive approach, which describes reality or facts based on the data obtained. Descriptive analysis techniques were used to explore the responses of SSB Putra Wirasaba members regarding the influence of football on their physical fitness. The research results show that regular football practice has a positive influence on improving physical condition, improving endurance, and improving the quality of participants' mental health. Thus, football can be an effective alternative in improving physical fitness and supporting the physical and mental well-being of SSB Putra Wirasaba members.